The Integration of Andragogy, Pedagogy, and Inclusive Technology in Language Education: A Systematic Literature Review of 21st Century Online Learning - Delsy Arma Putri; Syahrul R.; Agustina Agustina; Vivi Indriyani (Universitas Muhammadiyah Mataram, 2026)
The rapid growth of digital technologies has transformed online language learning, yet the integration of pedagogical structure and andragogic autonomy remains insufficiently synthesized. This study aims to systematically review how digital learning technologies are integrated with pedagogical and andragogical principles in online language learning and to develop an integrative conceptual framework. A PRISMA-guided systematic literature review was conducted on 15 peer-reviewed articles published between 2015 and 2025, selected using the PICOS framework. The analysis employed thematic synthesis to identify patterns of technology use, pedagogical approaches, and andragogic principles. The findings show that technologies such as learning management systems, mobile learning, artificial intelligence, and immersive environments function as mediating tools linking structured pedagogical scaffolding with learner autonomy. However, their effectiveness is highly context-dependent and constrained by instructional design and learner readiness. Based on the synthesis, this study proposes the Integrated Pedagogical–Andragogical (IPA) Model, which conceptualizes technology as an epistemic mediator facilitating a gradual transition from guided instruction to self-directed learning. This review offers an integrative theoretical contribution to digital language education without making generalized causal claims.